Pengaruh Harga dan Lokasi Terhadap Keputusan Pembelian Busana Muslim Oki Setiana Dewi Pada Butik Syar’I Haza Lahat - HAYANI HAYANI (Ekonomika, 2021)
One of the Muslim fashion outlets in Lahat City which was founded in 2020 that provides adult Muslim clothing, namely the Syar'i HAZA Boutique, which is here to meet the needs of the city of Lahat for Muslim fashion. The method used in this research is descriptive method,which is a problem solving by describing, interpreting and analyzing the data so that it can find the objective of the discussion effectively. Also using quantitative analysis, namely using the validity test, reliability test, normality test, heteroscedesity test. As for the population, as many as 300 consumers and the sample taken was 75 people. The hypothesis in this study is that there is a significant influence between the independent variables and the dependent variable. Based on the t value of Variable Price with t count> from t table or 5,503> 2,000, then H_0 is rejected, H_a is accepted, Location Variable with t count> from t table or 4,573> 2,000, then H_0 is rejected, H_a is accepted.From the results of the hypothesis test in the study, the decision taken is that H_0 is rejected, H_a is accepted, meaning that together the variables X1 and X2 The location as a whole has a significant effect on the variable (Y).